Peningkatan Prestasi Belajar dan Kemampuan Pemecahan Masalah Matematika dengan Model Problem Based Learning Siswa Kelas VII.5 SMP Negeri 18 Pekanbaru - Sri Ulfa Insani; Sity Rahmy Maulidya (Journal on Education, 2024)
The aim of this research is to improve learning achievement and problem solving skills in mathematics learning by implementing a problem based learning model in class VII.5 of SMP Negeri 18 Pekanbaru. This classroom action research was carried out in two cycles. The research subjects were 33 students in class VII.5. Data collection techniques use test and non-test techniques. The test is used to measure students' learning achievement and mathematical problem solving skills using objective questions and essay instruments. Non-tests are used to make observations and documentation. Data analysis techniques use qualitative data analysis and quantitative data analysis. In cycle I there were 19 people who completed it with an average score of 70,03 and in cycle II there were 26 people who completed it with an average score of 80,09. Based on the research results, there was an increase in learning achievement and mathematical problem solving skills of class VII.5 in the 2024/2025 academic year.